2017
DOI: 10.1021/acs.joc.7b00409
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Contribution of Tiglate and Cinnamate to Cytotoxicity of Ipomoeassin F

Abstract: An efficient synthetic route for ipomoeassin F and its tiglate-modified analogues was developed. The route features late-stage conformation-controlled highly regioselective esterification of the glucose diol in the disaccharide core. The results from the NCI-60 cell line screens of ipomoeassin F were reported for the first time. Moreover, two new C-3-cinnamoyl-Glcp analogues (2 and 3) were prepared. Their in-house cytotoxicity data convey an important message that both identity and positioning of the two α,β-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 22 publications
3
40
0
Order By: Relevance
“…Attracted by single-digit nanomolar IC 50 values against several cancer cell lines (Table 1), four total syntheses of ipomoeassin F have been accomplished by three independent research teams including ourselves. [59] In recent NCI-60 cell line screens, we further confirmed both high potency (the average GI 50 of ~30 nM) and potential novel functional mechanism (the correlation index < 0.5 in the compare analyses) of ipomoeassin F,[6] which suggests that the ipomoeassins are unique chemical space for studying biology. To accelerate future ipomoeassin research in chemical biology and even drug discovery, however, analogues that can be synthesized more easily but have biological activity similar or superior to ipomoeassin F are still highly desirable.…”
Section: Introductionsupporting
confidence: 69%
“…Attracted by single-digit nanomolar IC 50 values against several cancer cell lines (Table 1), four total syntheses of ipomoeassin F have been accomplished by three independent research teams including ourselves. [59] In recent NCI-60 cell line screens, we further confirmed both high potency (the average GI 50 of ~30 nM) and potential novel functional mechanism (the correlation index < 0.5 in the compare analyses) of ipomoeassin F,[6] which suggests that the ipomoeassins are unique chemical space for studying biology. To accelerate future ipomoeassin research in chemical biology and even drug discovery, however, analogues that can be synthesized more easily but have biological activity similar or superior to ipomoeassin F are still highly desirable.…”
Section: Introductionsupporting
confidence: 69%
“…To investigate this, we examined the published comparative growth inhibitory phenotypes across the cell lines assayed in the USA National Cancer Institute panel of 60 cancer cell lines (NCI-60) 38 against CbA, 3 AprA, 11 and IpoF. 39 This correlative analysis revealed that each of the three compounds was designated as “COMPARE-negative,” suggestive of having distinct cytotoxic mechanisms. While not all data from the two testing events for each compound were available, there were activity data from one test event for at least 55 cell lines in each case, out of a total of 61 different cell lines tested across the three compounds.…”
Section: Discussionmentioning
confidence: 99%
“…13 Intriguingly, ipomoeassins A and F (see Figure 1) have distinct cytotoxicity profiles, as revealed in the NCI 60-cell-line screen, suggesting that the ipomoeassins may possess an unusual mode of action. 16,17 On this basis, ipomoeassin F is a very promising candidate for molecular probe and even chemotherapeutic development; however, the absence of knowledge about the cellular targets of ipomoeassin F has significantly impeded such efforts. To overcome this challenge, after improving our understanding of the structure–activity relationship (SAR) of ipomoeassin F through medicinal chemistry studies, 1820 we employed a chemical proteomics approach to identify its binding partner(s) in human cells.…”
Section: Introductionmentioning
confidence: 99%